The role of informal caregivers in suicide prevention for men– findings from a psychological autopsy study - Laura Hofmann; Anna-Lena Springer; Birgit Wagner (BMC Public Health)
Abstract Background Men have a significantly higher risk of dying by suicide than women and at the same time are less likely to make use of psychosocial support services. Therefore, informal caregivers who care for a person at risk play a significant role. This study aims to highlight the distress and support needs of informal caregivers for men in suicidal crises. Methods N = 15 participants who lost a man to suicide in the last 3–12 months were interviewed using psychological autopsy interviews. The interviews were analyzed using a comprehensive category system while following a deductive-inductive approach. Results The majority of participants reported experiencing significant stress as well as anxiety about leaving the affected men unsupervised. Only four participants indicated that they openly discussed their stress with their social environment, and just two sought professional support. Notably, only two caregivers anticipated the possibility of suicide. There was also little professional support for caregivers, resulting in participants using internet resources to inform themselves about suicidal ideation and behavior. Conclusion These findings highlight the significant stress and burden experienced by informal caregivers in suicide prevention for men. Lack of open communication and insufficient access to support exacerbate the emotional burden on caregivers. These results highlight the need for accessible resources and assistance to better support both caregivers and the individuals they care for. Trial registration German Clinical Trials Register, DRKS00030758, Registered on 11.11.2022.